Inverse opals and waveguides to enhance optical absorption and efficiency of photovoltaic devices - Mayimele, Nhluvuko (My University, 2021)
Photovoltaic (PV) is an environmental friendly technology that promises efficient and effective harvesting of solar energy. Studies shows that, hydrogenated amorphous silicon (a-Si:H) has been used as photoactive and doped layers in thin-film solar systems, but its photo-conversion efficiency (PCE) is very low due to a thinner absorption layer and light degradation issues. To overcome these constraints, a better understanding of system structure, material properties, and device architecture is needed, as even a small increase in photocurrent has a major impact on photoconversion efficiency. The study explores the effect of using optically active layers onto amorphous silicon-based thinfilm solar cells such as plasmonic nanoparticles (NPs) and waveguides to modify the optical response. Incorporating spherical shaped silver (Ag) or gold (Au) nanoparticles (NPs) in PVs will take full advantage of surface plasmon resonance through the enhancement absorption and scattering of light. The metallic NPs were synthesized through wet chemistry, where hydrogen tetrachloroaurate (HAuCl4) was reduced in 1% trisodium citrate to produce Au NPs and with Ag NPs, silver nitrate (AgNO3) was reduced in 1% sodium citrate. The TEM and SEM images revealed 20 nm spherical Au/Ag NPs with plasmon resonance at 500 nm and 550 nm, respectively. Silica and titania nanoparicles were synthesized through sol-gel process, in which tetraethylorthosilicat (TEOS) and titanium tetraisopropoxide (TTIP) were reduced in an ethanolic solution, respectively. SEM images revealed spherically shaped NPs for both SiO2 and TiO2 with varying sizes. They both showed absorption resonance at 550 nm and 680 nm, respectively, with absorption intensity increasing, accompanied by blue i shift, as the size of the nanospheres increases (same trend is observed by Tsekov et al [1]). The Ag@TiO2, Ag@SiO2 and Au@SiO2 core–shell NPs were also synthesized by sol-gel technique (modified Stöber method), TEM images showed 58 nm spherical coreshell NPs having a shell thickness of about 20 nm and core of 20 nm for Ag@SiO2 and Au@SiO2 core-shell NPs. They showed a plasmon resonance at 500 nm and 550 nm respectively, with a higher absorption intensity, while spherical 50 nm Ag@TiO2 coreshell NPs showed multiple plasmon resonance between 500 nm and 650 nm. Furthermore, waveguides were studied where Silica (SiO2), Titania (TiO2) and SiO2:TiO2 waveguides films were fabricated through sol-gel technique. The wavegiudes thickness was varied from 30 nm to 300 nm. They also showed a transmittance between 30% and 60% at 460 nm and also exhibited absorption at 450 nm to 500 nm, as result of the film thickness increase. The surface plasmon resonance by Ag/Au NPs and core-shell NPs (Ag@TiO2, Ag@SiO2, TiO2, SiO2) has been modelled using MATLAB software based on Mie theory, to calculate the absorption and scattering cross-sections. The simulations showed spherical Ag/Au NPs and Ag/Au@SiO2 core-shell NPs have plasmon resonance between 400 nm and 550 nm respectively, with an increased absorption intensity. The Ag/Au@TiO2 core-shell NPs showed a plasmon resonance between 500 nm and 750 nm respectively, also an improved absorption intensity. The optical absorption from simulation for Ag@SiO2 core-shell NPs is in good agreement with experimental data for the same core-shell dimensions and structures. The PV performances of a-Si solar cells incorporated with metallic NPs, core-shell NPs and waveguide were investigated. The result revealed that the PCE of the PV devices were all significantly enhanced due to the plasmonic effect of the noble metal nanostructures. For example, Under AM1.5 illumination, a PCE of 9.86% was obtained in a-Si solar cell incorporated with Ag@TiO2 core-shell NPs, while a reference a-Si solar cell had a PCE of 6.73%. The PCE of a-Si solar cell incorporated with SiO2 waveguide was increase to 7.53%, which is a good improvement compared to the reference a-Si solar cell with the PCE of 6.74% this might have occurred due to the carrier recombination ii resulting from the fill factor which improved from 50% up to 55%. Finally, numerical modelling of crystal-silicon (c-Si) solar cell was studied as to improve the photon absorption efficiency. Device simulations were carried out by solving Poisson equations for multi-dimensional systems incorporating Plasmonic resonance dependent core-shell NPs or nanostructures to calculate drift and diffusion currents. The c-Si solar cell were incorporated with Ag@TiO2, Ag@SiO2, TiO2, SiO2 core-shell NPs and Ag NPs at the top/front end of the device, to promote photon/light trapping and or forward scattering on the device. The simulation showed an increase on the flow of current as the core-shell NPs were introduced onto the device and each of these core-shell NPs had a unique absorption coefficient. The results predicted the highest increase in PCE of 28.05% in a c-Si solar cell with Ag@TiO2 core-shell NPs.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Chemistry, University of the Witwatersrand, 2021